2019
DOI: 10.1021/acsmedchemlett.8b00597
|View full text |Cite
|
Sign up to set email alerts
|

Chromenopyrazole-based High Affinity, Selective Fluorescent Ligands for Cannabinoid Type 2 Receptor

Abstract: Cannabinoid type 2 receptor (CB 2 R) is an attractive target for the treatment of pain and inflammatory disorders. Availability of a selective CB 2 R fluorescent ligand to study CB 2 R expression and localization in healthy and disease conditions would greatly contribute to improving our understanding of this receptor. Herein, we report a series of chromenopyrazole-based CB 2 R fluorescent ligands. The highest affinity fluorescent ligand was Cy5-containing 24 (hCB 2 R pK i = 7.38 ± 0.05), which had 131-fold se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…[20][21][22] Several fluorescent ligands targeting CB2R have been reported. [23][24][25][26][27][28][29][30][31][32][33][34][35] However, in our collective experience the published probes perform less than optimally as judged by at least one of the following criteria: modularity of design for multiple applications, selectivity over CB1R, affinity and specificity for CB2R, photophysical properties, and applicability across species, techniques, and cell types. Furthermore, bifunctional probes that require additional manipulations prior to imaging are often incompatible with live cells.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Several fluorescent ligands targeting CB2R have been reported. [23][24][25][26][27][28][29][30][31][32][33][34][35] However, in our collective experience the published probes perform less than optimally as judged by at least one of the following criteria: modularity of design for multiple applications, selectivity over CB1R, affinity and specificity for CB2R, photophysical properties, and applicability across species, techniques, and cell types. Furthermore, bifunctional probes that require additional manipulations prior to imaging are often incompatible with live cells.…”
Section: Introductionmentioning
confidence: 99%
“…A cAMP BRET assay showed that the compound acted as an inverse agonist and widefield microscopy imaging showed plasma membrane staining with no detectable intracellular uptake. Furthermore, signal displacement in presence of SR144528 was observed as well [159] …”
Section: Fluorescent Ligands For Gpcrsmentioning
confidence: 84%
“…[148] Coupled with three different fluorophores, BODIPY-630/650, BODIPY-FL, and Cy5, the phenolic chromenopyrazole scaffold was utilised for potential CB fluorescent ligands. [125] The C-4 position of the phenyl was found to have better linker tolerance and higher affinity to CB 2 R. Using BODIPY-630/650 as the fluorophore, the binding affinity (pK i (CB 2 R) ¼ 5.80 AE 0.12) was deemed too low to be useful for imaging studies. Extending the PEG linker from 2 to 5 showed no improvement to the fluorophore's imaging potential or selectivity for BODIPY-630/ 650.…”
Section: Fluorescent Classical Cannabinoid Derivativesmentioning
confidence: 99%